SUICIDE AS A PHENOMENON IN THE MUNICIPALITY OF PRIZREN FROM CITIZENS’ PERSPECTIVE - Alban KRYEZI (Prizren Social Science Journal, 2022)
Suicide as a phenomenon is present in almost all societies of the world, including the Kosovar society, through which the individual tries to take his own life. According to the law, this offense is not punished because the individual ceases to exist as a legal subject, but if we are dealing with pushing or assisting suicide, then investigations are initiated by the competent authorities.